Male-derived PBP4 is essential for sperm competition by mediating sperm motility in moths - Yu He; Qi Yan; Jing-Hao Hou; Ying Li; Zhi-Qiang Wei; Jin-Meng Guo; Nai-Yong Liu; Markus Knaden; Bill S. Hansson; Shuang-Lin Dong; Jin Zhang (Proceedings of the National Academy of Sciences, 2025)
Male moths rely on antennal olfactory sensilla to detect female-emitted sex pheromones during mate localization, a process critically mediated by pheromone-binding proteins (PBPs) that facilitate ligand transport to dendritic membrane-bound pheromone receptors. Intriguingly, a divergent PBP paralog (PBP4) in noctuid moths has been identified exhibiting predominant expression in the male reproductive system, though its functional significance remained elusive. In this study with Spodoptera exigua , we demonstrated that PBP4 is specifically expressed in male accessory glands (MAGs) and transferred to females during copulation. CRISPR-mediated PBP4 knockout (PBP4 −/− ) significantly reduced male reproductive success via impaired sperm competition, evidenced by diminished offspring sired. Transcriptomic and qPCR analyses revealed expressional correlation between PBP4 and the odorant receptor coreceptor (Orco), and similar sperm competition deficits were observed in Orco −/− males. Furthermore, both mutants exhibited compromised sperm motility and reduced sperm transfer from spermatophores to spermathecae. In vitro sperm motility assays showed that a specific agonist of Orco, VUAA1, robustly enhanced sperm motility in an Orco-dependent manner. Analyses of four additional moth species, including noctuids and non-noctuids, revealed a similar specific expression in the male reproductive tracts in all of them. Our findings unveil a noncanonical role for PBP4 in reproductive fitness and evolutionary conservation of the PBP-OR signaling pathway.